Case Report: Migraine-Like Headache With Visual Aura Initiated by Endovascular Coiling Treatment for a Posterior Cerebral Artery Aneurysm - Chen, Xin; Zhang, Juan; Li, Han-Li; Deng, Zi-Ru; Wang, Long; Cao, Li; Xie, Cheng-Juan; Wang, Yu (Frontiers in Neurology, 2021)
Cervical, anterior and middle cerebral artery aneurysm is a causative factor for migraine and endovascular treatment usually improves migraine headache. Posterior cerebral artery (PCA) aneurysm is a rare condition and its association with migraine is very rarely reported, and endovascular coiling treatment causing migraine-like headache has never been reported. Here, we describe a newly developed migraine-like headache with visual aura after endovascular coiling treatment for PCA aneurysm in a 31-year-old female patient. One month after the endovascular therapy, the patient stopped using antiplatelet agents of clopidogrel and aspirin and presented episodic headache attack twice a month, with typical migraine features including visual aura, right-sided temporal throbbing pain accompanied with nausea, vomiting and photophobia. And the recurrence of migraine-like headache with visual aura was terminated by clopidogrel administration. The generation of the migraine-like headache with visual aura is probably associated with microemboli due to endovascular coiling. This case supports the hypothesis that migraine with aura can be associated with microemboli of variant origins.